2019
DOI: 10.3390/nu11010150
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Nutritional Status in Patients with Cystic Fibrosis

Abstract: Background: Zinc is an essential nutrient for all forms of life and its deficiency affects the normal growth and development of human beings. Objective: The main aim was to investigate zinc nutritional status by serum zinc concentration (SZC) and dietary zinc intake and their association in cystic fibrosis (CF) patients. Methods: A cross-sectional study was conducted in CF patients. Anthropometric measurements and respiratory and pancreatic tests were conducted. Hypozincemia was determined by SZC while using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 83 publications
(129 reference statements)
2
30
1
1
Order By: Relevance
“…Detailed study methods regarding assessing zinc nutritional status in this series are reported elsewhere. Briefly, this nutritional study included an assessment of phenotypic characteristics, a blood test, a dietary survey, and a specific assessment of respiratory and pancreatic functions [30]. Figure 1 shows the flowchart of this cross-sectional study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed study methods regarding assessing zinc nutritional status in this series are reported elsewhere. Briefly, this nutritional study included an assessment of phenotypic characteristics, a blood test, a dietary survey, and a specific assessment of respiratory and pancreatic functions [30]. Figure 1 shows the flowchart of this cross-sectional study.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the flowchart of this cross-sectional study. In this series, the genotype of the participants, as well as the Norman-Crispin score (>5), the forced vital capacity (FVC% < 80%) and the forced expired volume in 1 s (FEV1 < 80%) to estimate respiratory sufficiency (SR) and insufficiency (IR), and the fat absorption coefficient (CFA > 94%) to evaluate pancreatic sufficiency (PS) and insufficiency (PI) were studied and published [30]. An abdominal ultrasound was taken to assess the digestive tract status.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc deficiency in infants and children has been known to cause malabsorption and loss of appetite (Monge et al, 2019). In addition, it leads to dry skin, , 2004).…”
Section: Discussionmentioning
confidence: 99%